2005
DOI: 10.1161/01.atv.0000149675.83552.83
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatides Activate Platelets Through P-Selectin and Enhance Platelet and Platelet–Leukocyte Aggregation

Abstract: Objective-Sulfatides are sulfated glycosphingolipids present on the surface of a variety of cells; however, their exact physiological function is not known. Recently, we have shown that the inhibition of sulfatide-P-selectin interactions leads to disaggregation of platelet aggregates. Methods and Results-In this study, we show that sulfatides activated platelets as they increased activation of GPIIb/IIIa (PAC-1 epitope) and expression of P-selectin on the platelet surface. Furthermore, sulfatides aggregated wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
48
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 33 publications
9
48
1
Order By: Relevance
“…Interestingly, sulfatides were found to facilitate P-selectinmediated platelet adhesion and aggregation (Merten and Thiagarajan 2001). The recent finding that sulfatides could lead to platelet activation and their aggregation with leukocytes suggest this mechanism to play an important role in hemostasis and thrombosis (Merten et al 2005). In this context, our finding that murine colon carcinoma cells carrying sulfatides can effectively induce P-selectin-mediated platelet aggregation raises the possibility for the involvement of these interactions also during hematogenous metastasis.…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, sulfatides were found to facilitate P-selectinmediated platelet adhesion and aggregation (Merten and Thiagarajan 2001). The recent finding that sulfatides could lead to platelet activation and their aggregation with leukocytes suggest this mechanism to play an important role in hemostasis and thrombosis (Merten et al 2005). In this context, our finding that murine colon carcinoma cells carrying sulfatides can effectively induce P-selectin-mediated platelet aggregation raises the possibility for the involvement of these interactions also during hematogenous metastasis.…”
Section: Discussionmentioning
confidence: 75%
“…A similar amplification loop exists for sulfatides, which interact with P-selectin on activated platelets to enhance further platelet activation and P-selectin expression. 69 This interaction pathway also recapitulates the cooperativity between P-selectin and ␣ M ␤ 2 in mediating PMN-endothelial cell conjugation; engagement of PSGL-1 on PMNs with P-selectin on endothelial cells results in PMN rolling and ␣ M ␤ 2 activation (reviewed in McEver and Cummings 70 ). However, because blockade of ␣ M ␤ 2 /GPIb␣ results in only approximately 50% reduction of platelet activation, a second independent pathway for MP activation of platelets is also likely to exist and could involve platelet agonists, which are reported to be present in PMN-derived MPs.…”
Section: Discussionmentioning
confidence: 80%
“…Sulfatide was also identifi ed as an interacting partner of P-selectin and promoted a P-selectinmediated metastasis process in colon cancer cells ( 20 ). Sulfatide and P-selectin interactions led to subsequent platelet aggregation ( 21 ) and played an important role in the formation of cancer embolus. Our previous study ( 15,18 ) revealed that hepatoma cells expressed sulfatide after CST transfection.…”
Section: Plasmid Constructionmentioning
confidence: 99%